Oligomer Resveratrol dari Kulit Batang Shorea assamica Dyer (Dipterocarpaceae) dan Sitotoksitasnya - Sahidin Sahidin; Euis Holisotan Hakim; Yana Maolana Syah; Lia Dewi Juliawaty; Sjamsul Arifin Achmad; Nordin Hj Lajis (Institut Teknologi Bandung, 2007)
Four resveratrol oligomers which consist of two resveratrol trimers, i.e., vaticanol A (1) and Î±-viniferin (2), and two resveratrol tetramers, i.e., vaticanol B (3), and isohopeafenol (4) have been isolated from acetone extract of the stem bark of Shorea assamica Dyer. The elucidations on the structure of these four compounds were based on the spectroscopic data, including UV, IR, 1-D and 2D NMR spectra, and comparison with related data reported previously. Cytotoxicity of the isolated compounds against murine leukemia P-388 cells exhibited that vaticanol A (1), Î±-viniferin (2), vaticanol B (3) dan isohopeaphenol (4) had IC50 of 27.0, 17.5, 46.4, and 36.0 ppm, respectively. The results showed that cytotoxicity of resveratrol trimers were relatively higher than resveratrol tetramers.